Pengembangan Bingo sebagai Media Pembelajaran Sejarah di SMA - Anisa Oktiani; Hera Hastuti (Jurnal Kronologi, 2020)
This research is motivavailabated by the unavailability of enjoyable history learning media, but still can help students in higher-order thinking that is analytical thinking. Based on observations made by students look bored ini following the history of learning so that it inhibits students in understanding the material to reach a igh level of thinking that is analytical thinking.This research aims to develop bingo as a history learning media that is feasible to use. Developing bingo media like bingo games. This research is a research and development of R&d, by following the steps of developing the ADDIE model. But in this study the research procedure was carried out only at the development stage, due to the limited time of the researcher. In this study the validity test is study the validity test is based on the assessment of material experts and media experts using a questionnaire to assess the feasilibity of the media. Reseacrh data were analyzed with quantitative analysis techniques. The results of the study showed that the feasibility of the media based on the assessment of material experts was 3,57 and the assessment of media experts was 3,5. This shows that the bingo media ini history learning is very feasible to use.